The relationship between daily spiritual experiences and the dimensions of spiritual care competence in nursing students: The dimension of professionalization and improvement of the quality of spiritual care - Fatemeh Estebsari; Abdollah Farhadi Nasab; Mohadaseh Barati; Sara Stiri; Marjan Moradi Fath; Davoud Mostafaie; Zahra Rahimi Khalifeh Kandi (Iranian Journal of Nursing and Midwifery Research, 2023)
Background: Daily spiritual experiences and spiritual care competence have positive health effects on patients and form an integral part of the nursing profession. This study was conducted to determine the relationship between daily spiritual experiences and the dimensions of spiritual care competence in nursing students. Materials and Methods: This cross-sectional study was conducted on 401 nursing students in their last year of the program. The participants were selected from nursing schools in Tehran Province, Iran, in the academic year 2019–2020. The required data were extracted using a demographic information questionnaire, the Daily Spiritual Experiences Scale (DSES), and the Spiritual Care Competence Scale (SCCS). The collected data were analyzed in SPSS software at the significance level of 0.05. Results: The mean (SD) of daily spiritual experiences and total spiritual care competence was 67.15 (16.33) and 101.77 (16.26), respectively. The personal support and patient counseling dimensions had the highest mean (SD) [22.10) 4.80)]. Among all these dimensions of spiritual care competence, only professionalization and improvement of the quality of spiritual care were predictors of the students' daily spiritual experiences (p < 0.05). Conclusions: The professionalization dimension of spiritual care competence was identified as a predictor of daily spiritual experience in nursing students. Therefore, the researchers recommend the highlighting of this dimension in nursing programs to promote the students' spiritual care competence.